PRODUCTIVITY OF PINTO BEANS (Arachis pintoi) WITH DIFFERENT TYPES AND DOSAGE OF ORGANIC FERTILIZER - N. M., Witariadi; Candraasih K., N. N. (Majalah Ilmiah Peternakan; Vol 22 No 2 (2019): Vol. 22 No.2 (2019), 2019)
The study aims to determine the productivity of pinto beans (Arachis pintoi) which is fertilized with different types of organic fertilizer including its dosage. The study was conducted by using a completely randomized design (CRD) within two patterns of factors. Firstly, organic fertilizers are cow dung (S) and chicken manure (A). Secondly, dosages without fertilizer (D0), 15 tons/ha dosages (D1), 20 tons/ha dosages (D2), dosage of 25 tons/ha (D3); and dosage of 30 tons/ ha (D4) of organic fertilizers. The variables observed were plant height, number of branches, number of leaves, leaf dry weight, stem dry weight, total forage dry weight, leaf areat and leaf dry weight ratio with stem dry weight. The results showed no interaction between the type and dosage of fertilizer in which the growth and production of pinto beans (Arachis pintoi) gave the same results by fertilizing with 25-30 tons/ha dosages of chicken manure. It can be concluded that increasing the productivity of pinto beans (Arachis pintoi) can be fertilized with 25-30 tons/ha dosages of chicken manure